Colombia´s Special Jurisdiction for Peace, use of Case concept within their decisions and harm to procedural guarantees - Fernanda NAVAS-CAMARGO3Daniel Ricardo Vargas Diaz, (Opción, 2020)
Transitional Justice should provide war victims with tools that attain their dignity and lead to acknowledgement of the violations occurred, so to prevent further perpetrations of human rights. Installment of the Special Jurisdiction for Peace (SJP)4 was made in March of year 2018 and the first judgements lead to question the accuracy of their interpretation and application of concepts in their court decisions, i.e. Case. This paper aims to criticize the submission of the term, to make visible the harm being made because of wrongful application and breach of the procedural guarantees from international standards of judgement